Bibliotheken der Schweiz: Innovation durch Kooperation Festschrift für Susanna Bliggenstorfer anlässlich ihres Rücktrittes als Direktorin der Zentralbibliothek Zürich - Zentralbibliothek Zürich; Keller, Alice; Uhl, Susanne (De Gruyter, 2018)
This volume presents a representative selection of initiatives of the Swiss Academic Libraries, which show a high innovation potential as a result of successful cooperation. The focus is on science, higher education and funding policy topics in connection with research support services such as national open access strategy, research data management, digitization and presentation and service platforms. Also addressed are issues of structural development and strategic location planning, education and training or the importance of national and national associations. The volume will be published as a Festschrift for Susanna Bliggenstorfer on the occasion of her resignation as director of the Zentralbibliothek Zürich.